Simulation Training for Operational Medicine Providers (STOMP): Design and Implementation of a Novel Comprehensive Skills-Based Curriculum for Military General Medical Officers - Polk, Travis M; Greer, Joy; Alex, John; Kiser, Rebecca; Gunzelman, Kim; Petersen, Carl; Spooner, Michael (Military medicine, 2018)
Abstract Background Fifty percent of graduating U.S. Navy post-graduate year (PGY)-1 physicians will practice in the operational environment before returning to residency training. However, current internship structure is less rotational and focuses more on specialty-specific training. Therefore, these physicians may not be fully prepared for this primary care role. Methods Based on the U.S. Navy privileges for General Medical Officers, a comprehensive didactic and simulation curriculum was developed. Twenty-three procedural skill competencies (SK) and five validated standardized patient (SP) scenarios were identified. During the SK portion, learners reviewed instructional videos, read reference materials, and practiced with partial task trainers before small-group sessions with subject matter experts (SME). Separate SP round-robin sessions were conducted and feedback provided by SMEs and SPs. Learners demonstrated competency or were remediated. Results One hundred and three PGY-1 trainees participated over 2 yr. All trainees met requirements during the SK phase. During the SP phase, seven learners required remediation. All learners ultimately met requirements for privileging. Conclusion The Simulation Training for Operational Medicine Providers curriculum for future General Medical Officers is an effective tool for primary care skill training and credentialing. Plans for export to other Graduate Medical Education sites are underway and further evaluation of skills retention is warranted.